Corporate Social Responsibility (CSR) Strategy in The Oil and Gas Sector: Insights From PT Migas Hulu Jabar Offshore North West Java (PT MUJ ONWJ) - Ubaydillah, Ubaydillah; Suhendi, Suhendi; Sari, Linda Karlina (Business Review and Case Studies, 2025)
Background: Corporate Social Responsibility (CSR) has become a crucial component of business strategies, particularly in industries with significant environmental and social implications, such as oil and gas. PT Migas Hulu Jabar Offshore North West Java (PT MUJ ONWJ) manages a 10% Participating Interest (PI) fund to implement CSR programs aimed at driving socio-economic and environmental development. However, existing CSR practices in this sector often face challenges, such as weak stakeholder engagement, fragmented resource allocation, and limited sustainability, which create uncertainty in determining effective strategic priorities.Purpose: This study aims to determine priority CSR strategies at PT MUJ ONWJ by evaluating key criteria and sub-criteria to ensure effective and sustainable impact through CSR initiatives.Design/methodology/approach: The Analytical Hierarchy Process (AHP) was employed to assess four main criteria Economic, Social, Environmental, and Program Sustainability along with 12 corresponding subcriteria. Stakeholder alignment analysis was also conducted to measure consensus levels across different interest groups. Data were collected from nine purposively selected respondents, consisting of internal and external stakeholders, chosen for their expertise and direct involvement in Participating Interest (PI) management.Findings/Result: The analysis identified Program Sustainability as the top priority (0.2769), followed by environmental (0.2494), economic (0.2441), and social (0.2296) aspects. Sub-criteria, such as Financial Continuity (0.3673) and Natural Resource Management (0.3995) were found to be the most influential. However, the low consensus value (W = 6%) indicates divergence in stakeholder preferences regarding CSR focus areas, reflecting differing priorities among internal company stakeholders, government authorities, and local communities. This suggests the need for more structured stakeholder engagement and consensus-building mechanisms to harmonize perspectives in strategic CSR planning.Conclusion: The results underscore the importance of enhanced stakeholder engagement and strategic resource allocation in improving the effectiveness and sustainability of CSR programs in the oil and gas sector. Specifically, the AHP findings highlight Program Sustainability and Environmental Management as key priorities, providing a clear roadmap for PT MUJ ONWJ to allocate its participation interest (PI) funds more effectively toward financial continuity, innovation, and natural resource management in future CSR initiatives.Originality/value (State of the art): This study offers a structured decision-making framework using AHP to prioritize CSR strategies in the context of Participating Interest management, providing valuable insights for CSR implementation in resource-intensive industries, especially in developing countries.Keywords: analytical hierarchy process, corporate social responsibility, oil and gas industry, stakeholder engagement, sustainability